Accumulating the key proteomic signatures associated with delirium: Evidence from systematic review. - Md Parvez Mosharaf; Khorshed Alam; Jeff Gow; Rashidul Alam Mahumud (PLoS ONE)
Delirium is a severe neuropsychiatric illness that occurs frequently in intensive care and postoperative units which results in prolonged hospital stays and increases patient's mortality and morbidity rates. This review focused on accumulating the common key proteomic signatures significantly associated with delirium. We carried out a systematic literature review of studies on delirium proteomic biomarkers published between 1st January 2000 and 31st December 2023 from the following electronic bibliographic databases including PubMed, Scopus, and EBSCOhost (CINAHL, Medline). A total of 1746 studies were identified and reviewed, and 78 studies were included in our review. The PRISMA guidelines, the PEO framework, and JBI quality assessment method were followed in this review to maintain the inclusion and exclusion criteria and risk of bias assessment. Most of the included studies were of the cohort (68%) and case-control (23%) design. We have accumulated a total of 313 proteins or gene encoded proteins of which 189 were unique. Among the unique proteins, we focused on the top 13 most investigated proteins (IL-6, CRP, IL-8, S100B, IL-10, TNF-a, IL-1b, Cortisol, MCP-1, GFAP, IGF-1, IL-1ra, and NFL) that are significantly associated with delirium. Most of these are cytokines and inflammatory proteins indicating a strong interconnection with delirium. There was remarkable inconsistency among the studies in reporting the specific potential proteomic biomarker. No single proteomic biomarker can be solely used to diagnose and predict delirium. The current review provides a rationale for further molecular investigation of delirium-related proteomic biomarkers. Also, it's recommended to conduct further in-depth molecular research to decipher drug target biomolecules for potential prognostic, diagnostic, and therapeutic development against delirium.